Hegelian Political Heritage in the United States: How Hegel’s Political Theory Influenced the Transformation of American Freedom and the State in the Twentieth Century - Sweeney, Tys M. (Tufts Archival Research Center, 2021)
This study examines the philosophic and political challenge offered by mid-twentieth century progressivism and liberalism to the prevailing Lockean tradition of individualism and limited government in America. I examine the impact of G. W. F. Hegel’s political philosophy — especially his notions of positive liberty and the positive state — on John Dewey, Herbert Croly, and other founding philosophers of the American progressive movement. I explore how this new vision of political development informed the transformational state building efforts and social policies of the New Deal and post-war Liberal Consensus. I show that that despite progressive liberalism’s own internal contradictions and powerful conservative opposition, this new governing philosophy established a political heritage, state structures, and policies that survive today.; Advisor: Professor Robert Devigne